Clinical and economic burden of preseptal cellulitis in children: a 6-year review - Özbakır, Çağla; Ergün, Deniz; Kaçar, Pelin; Kahraman Çetin, Berna; Özbakır, Hıncal; Özer, Arife; Güner Özenen, Gizem; Akaslan Kara, Aybüke; Orbatu, Dilek; Bayram, Nuri; Devrim, İlker (The Turkish Journal of Pediatrics, 2026)
Background. Children diagnosed with preseptal cellulitis frequently require hospitalization, leading to both clinical management challenges and substantial healthcare-related costs. The condition often necessitates intravenous antibiotic therapy, radiological imaging, laboratory tests, consultations, and inpatient care, which collectively contribute to the overall economic burden. However, data on the clinical characteristics and cost distribution among pediatric patients remain limited. This study aimed to evaluate both the clinical and economic burden of preseptal cellulitis in hospitalized children and to identify the clinical factors influencing healthcare costs. Methods. This retrospective study included children aged 1 month to 18 years who were hospitalized with a diagnosis of preseptal cellulitis between January 2019 and December 2024. Patients were grouped according to age and presence of predisposing factors. Length of stay, total hospital costs, and cost components were analyzed based on clinical characteristics. Results. A total of 166 patients were included (mean age: 70.1 ± 46.9 months; 62% male). The most common findings were periorbital swelling (96.4%) and erythema (75.3%). Median length of stay was 5 days, with no significant differences by age, sex, or predisposing factors (p>0.05). However, a strong positive correlation was found between length of stay and total cost (rho=0.775, p